Cultural Harmony in Motion: Revealing the Communication Prowess of Saung Angklung Udjo Community in Enriching Local Traditions - Angelo, Eldorado Aluzio; Mujiono, Mujiono; Alvin, Silvanus (Dinasti Publisher, 2023)
The research explores Saung Angklung Udjo's strategic communication practices, highlighting their successful preservation and promotion of traditional Indonesian culture in the digital age. Aligned with Machfoedz's communication principles, Saung Angklung Udjo crafts a dynamic strategy merging cultural preservation with modern marketing techniques. The study underscores the significance of Saung Angklung Udjo's strategy, harmonizing content and form to engage diverse audiences. Kang Puji Yanandra's insights reveal a meticulous process emphasizing clear objectives, target markets, and tailored messaging. Saung Angklung Udjo's storytelling coupled with diverse media platforms practically translates theoretical principles. Furthermore, the research underscores Saung Angklung Udjo's adeptness in addressing consumer needs through precise information communication. Merging emotional appeal and factual data, Saung Angklung Udjo effectively conveys cultural significance, creating a meaningful connection between audience and heritage. The creative strategy and media selection exemplify Machfoedz's theories, creatively engaging audiences and countering cultural appropriation. The @InfoWisataBandung Instagram case study showcases the synergy of traditional and digital channels in reinforcing the cultural message. Beyond Saung Angklung Udjo, the study offers a model for cultural communities to safeguard heritage and engage wider audiences. By merging traditional and contemporary communication, Saung Angklung Udjo demonstrates the power of strategic communication in preserving cultural identity. Amid evolving digital landscapes, their success illustrates effective communication's potential in celebrating and sustaining cultural heritage.